GE_GERICHTE P/36/2021 vom 7. Februar 2025 - GE Cour de justice (2025)
IN DUBIO PRO REO;ASSASSINAT;TENTATIVE(DROIT PÉNAL);DÉSISTEMENT(DROIT PÉNAL);LÉGITIME DÉFENSE;VIOL;MENACE(DROIT PÉNAL);INJURE;FIXATION DE LA PEINE;CONCOURS D'INFRACTIONS;EXPULSION(DROIT PÉNAL);TORT MORAL | CP.112; CP.22.al1; CP.23.al1; CP.15; CP.190; CP.180; CP.177; CP.47; CP.49; CP.106a; CPP.122; CPP.126.al1.leta; CPP.116.al2; CO